2010
DOI: 10.1016/j.jpainsymman.2009.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Iyengar Yoga for Young Adults with Rheumatoid Arthritis: Results From a Mixed-Methods Pilot Study

Abstract: These preliminary findings indicate that IY is a feasible complementary approach for young people with RA, although larger clinical trials are needed to demonstrate safety and efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 17 publications
4
67
0
Order By: Relevance
“…144 145 One small randomized study of 30 young women with confirmed rheumatoid arthritis compared a six week Iyengar yoga intervention that was positively tested in a pilot study, 146 including yoga postures and relaxation for 90 minutes twice weekly, with usual care. 144 The study found some significant beneficial effect on pain acceptance, pain disability, and selected items of quality of life but not on pain intensity.…”
Section: Clinical Evidence For Mind-body Medicinementioning
confidence: 99%
“…144 145 One small randomized study of 30 young women with confirmed rheumatoid arthritis compared a six week Iyengar yoga intervention that was positively tested in a pilot study, 146 including yoga postures and relaxation for 90 minutes twice weekly, with usual care. 144 The study found some significant beneficial effect on pain acceptance, pain disability, and selected items of quality of life but not on pain intensity.…”
Section: Clinical Evidence For Mind-body Medicinementioning
confidence: 99%
“…Integrative modalities (sometimes referred to as complementary and alternative medicine) that have been described as effective in the management of pediatric pain include hypnosis, yoga, acupuncture, and massage [99,100,101,102,103,104,105,106,107]. Active mind-body techniques, such as guided imagery, hypnosis, biofeedback, yoga, and distraction each and all evoke pain modulation by engaging a number of mechanisms within the analgesic neuraxis.…”
Section: Interdisciplinary Rehabilitative Pediatric Pain Program: mentioning
confidence: 99%
“…However, these participants did not have clinical levels of depression or a chronic condition, and a longer intervention is appropriate for the present patient population. Most recently, we conducted a pilot study of a 6-week biweekly (90-minute classes) IYP for young adults with RA [82] and found significant reductions in pain and symptoms. It was therefore deemed suitable to strive for the maximum benefit in the shortest time likely to achieve benefit (6 weeks).…”
Section: Methodsmentioning
confidence: 99%
“…Based on our previous pilot work using Iyengar yoga for patients with rheumatoid arthritis [82], we estimated that yoga was likely to have a medium effect size on the primary outcomes. For power calculations, a freely-available software for power calculations - G*Power 3- was used to estimate the sample size needed for the estimated effect size using a pre/post by group interaction.…”
Section: Primary Outcomesmentioning
confidence: 99%